The Interplay of Service Recovery on Word of Mouth, Sustainable Brand, and Customer Trust in Banking - Cryzelda Minerva Lumbantoruan; Ronny H. Walean; Deske W. Mandagi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Customer trust is a fundamental factor in sustaining long-term relationships in the banking sector. However, service failures in digital banking can weaken trust and damage brand perception. This study examines the influence of service recovery on word-of-mouth, sustainable brand perception, and customer trust, and the mediating role of customer trust. Data were collected through a questionnaire survey from 250 banking customers in Manado, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that service recovery significantly influences word-of-mouth and customer trust. Word of mouth also significantly affects perceptions of a brand's sustainability and customer trust. Furthermore, customer trust mediates the relationship between service recovery and sustainable brand. These findings highlight the importance of effective service recovery in strengthening trust, generating positive word-of-mouth, and supporting sustainable branding in the banking industry.